2021
DOI: 10.1111/hsc.13555
|View full text |Cite
|
Sign up to set email alerts
|

The experience of the COVID‐19 pandemic for families of infants involved with Child Protection Services for maltreatment concerns

Abstract: The COVID‐19 pandemic and associated physical distancing restrictions have exacerbated social, economic and health disadvantage within our communities. With increases in mental health difficulties and family violence already being seen, there is concern that the risk of child maltreatment risk may also be increased. The current study aimed to explore the experience of the COVID‐19 pandemic for families identified to be at risk of child maltreatment in Victoria, Australia. Understanding the experiences of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
8
0
3
Order By: Relevance
“…The pandemic is considered to cause greater distress and risks of child abuse and neglect (Baldwin & De Young, 2021 ; Brown et al, 2021 ; Giannotti et al, 2021 ; Teo & Griffiths, 2020 ). Several scholars have raised arguments that victims of neglect, abuse and domestic violence have severely limited contact with the outside world during the pandemic, compromising their access to support and help (Campbell, 2020 ; Fogarty et al, 2021 ; Usher et al, 2020 ). Vogel et al ( 2021 ) found that psychological and physical well‐being decreased during the lockdown compared to before COVID‐19.…”
Section: Discussion and Concluding Thoughtsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic is considered to cause greater distress and risks of child abuse and neglect (Baldwin & De Young, 2021 ; Brown et al, 2021 ; Giannotti et al, 2021 ; Teo & Griffiths, 2020 ). Several scholars have raised arguments that victims of neglect, abuse and domestic violence have severely limited contact with the outside world during the pandemic, compromising their access to support and help (Campbell, 2020 ; Fogarty et al, 2021 ; Usher et al, 2020 ). Vogel et al ( 2021 ) found that psychological and physical well‐being decreased during the lockdown compared to before COVID‐19.…”
Section: Discussion and Concluding Thoughtsmentioning
confidence: 99%
“…This effect was felt even more strongly by vulnerable children and families due to school closures, the loss of access to social safety nets and impacts on Child Protective Services (CPS) (Cuevas‐Parra, 2021 ; Katz et al, 2021 ; Kelly & Hansel, 2020 ; Usher et al, 2020 ). Families already experiencing disadvantages may be most at risk of negative social, economic and health outcomes (Fogarty et al, 2021 , p. 2). Scholars have highlighted that children and families in CPS are the most vulnerable groups (Bolborici, 2020 ; Peet & Teh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, since the start of the pandemic, precisely this social support has been only very limited or not possible at all. Moreover, a recent study in Australia demonstrated that in the course of the pandemic, covering the cost of basic needs, such as food and rent, became such an overriding everyday concern that in a survey of families with children rated at risk of maltreatment before the pandemic "the impact of the pandemic on the well-being of children was not a prominent theme for parents" [104] (p. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Other international studies have reported similar results (Langley et al, 2021; Singer & Brodzinsky, 2020); however, the longer‐term effects of this disruption on these relationships are currently unknown. Australian parents with children in OOHC have also reported the distressing nature of reduced or no contact (Fogarty et al, 2022). Yet there is also evidence of efforts being made by service providers to implement supportive practices and increase communication to vulnerable families and children (Seay & McRell, 2021; Wilke et al, 2020).…”
Section: Discussionmentioning
confidence: 99%